The potential of community–based ecotourism (CBE) of mangrove ecosystem in Kota Marudu, Sabah - Hamid, Mohamad Zabidi; Abd. Ghani, Awang Noor; Mohd, Abdullah; Musa, Fazilah; Zulkifli, Mohd Fauzi (Program Pemindahan Ilmu - Kementerian Pendidikan Malaysia, 2013)
Mangrove ecosystem provides significant socio-economic benefits to human being, both directly and indirectly. One of its important contributions is for ecotourism development. The mangrove ecosystem in Kota Marudu, Sabah has great potential for community-based ecotourism despite its less developed districts in Sabah. Community-based ecotourism would be one way of creating employment opportunities for local community to improve their standard of living. Its success could be archived by three ways, i.e., support and participation of local people, provides economic benefits and protect local cultural identity and the natural environment. Survey was conducted to 346 persons of local respondents and 252 persons of non-local respondents using random sampling technique. This paper discusses the perception of local community and non-residence population of Kota Marudu about the potential ecotourism site development as ecotourism destination. The results revealed that the respondents interviewed (83.3%) would be willing to visit Kota Marudu after they were informed and shown on the information and pamphlet of mangrove and coastal resources of Kota Marudu. The local community would also be willing to participate in ecotourism activities such as river and bay cruises, homestay, recreational fishing, cultural and small business. The majority of the non-residence respondents were interested in ecotourism activities and stay in Kota Marudu for two days as well as would be willing to pay for ecotourism activities. However, only few respondents (11.11%) have prior knowledge about the potential of mangrove or Marudu Bay. The study also found that lack of promotion and package tour in ecotourism activities could be significant factors in ecotourism development of Kota Marudu (25.40%). Community-based ecotourism in Kota Marudu can be promoted through active participation of local community and support from both the government and private sectors. Hence, more effective promotion of Kota Marudu as an ecotourism destination should be pursued to make this area well-known and appear in tourism map of Sabah and Malaysia.